Determination of protein in goat milk by different analytical methods (Revista de Ciências Agroveterinárias, 2020)
The objective of this study was to correlate the Biuret, Lowry, Bradford, and Mlikoscan methods used to determine the level of protein in goat's milk and compare them with the Kjeldahl method. Milk samples collected from 18 goats of breeds Saanen (n=5), Anglo-Nubian (n=4), Pardo-alpina (n=5), and Creole (n=4) were analyzed. Correlation analyses between the different methods were performed using the Pearson test and the protein content between different breeds was compared using ANOVA. Total protein (TP) and casein (CN) concentrations obtained by all methods studied were positively correlated with the Kjeldahl method (p
Keywords: Biuret; Bradford; Kjeldahl; Lowry; goats